Explore and evaluate organisational culture aspects that affect lean implementation within manufacturing SMEs: the case of Saudi Arabia. (27th April 2020) - Alkhoraif, Abdullah A.; McLaughlin, Patrick
There is a scarcity of research about cultural aspects and organisational culture related to lean implementation (LI) (Pakdil and Leonard, 2015). In order to addressing the need for organisational culture (OC) to better facilitate lean and propel its success among small and medium enterprises (SMEs) in Saudi Arabia as a case, requires a methodology which supports the research and analysis of OC. Grounded theory, action research and an inductive approach has been selected. Due to the nature of the topic requiring the exploration of culture, it is beneficial to utilise qualitative research which is provided by grounded theory that has been adopted. Thus, adhering to the grounded theory process utilising an issue focused approach (Sackmann, 1991). Semi-structured interviews, observations and focus-groups were chosen to conduct this exploratory study. 37 aspects have been identified from semi-structured interviews. All these aspects have been aggregated through focus groups to seven main themes.